Gambaran Strategi Pembelajaran Instruktur Program Pelatihan Tata Busana di Lembaga Keterampilan Wanita - Sari, Dewi Purnama; Aini, Wirdatul (Penerbit Aksara Rentaka Siar (ARS), 2019)
This research was motivated by the phenomenon of the success of the fashion program at the Modeste Dolly Women's Skills Institute in the City of Bukittinggi. This is evidenced by the good learning outcomes of the learning community. Researchers suspect that the cause of the success of the fashion program occurred because of the good learning strategies used by the instructor. This type of research is quantitative descriptive research. The population in this study were 55 people studying fashion programs. The sampling technique used is cluster sampling. Samples were taken in each class as much as 50%, namely as many as 28 people. The technique of collecting data uses a questionnaire. While the data collection tool uses a list of statements. The data analysis technique uses a percentage formula. The results showed that the instructor's learning strategy from aspects (1) of learning activities, (2) learning methods, (3) learning media were categorized as very good. This is evidenced by the majority of learning citizens expressing